Coupling of a Liquid Organic Hydrogen Carrier system with industrial heat - Krieger, Christoph; Müller, Karsten; Arlt, Wolfgang (Chemical Engineering & Technology, 2016)

Thermodynamic analysis of reversible hydrogenation for heat storage in concentrated solar power plants - Krieger, Christoph; Müller, Karsten; Arlt, Wolfgang (Solar Energy, 2016)
Heat storage in concentrated solar power plants is required to compensate for variable availability of solar radiation. The energy density achievable with thermochemical heat storage is higher than for molten salt which represents the state of the art technology. The efficiency of different reversible hydrogenation reactions as thermochemical heat storage systems have been examined, since they can be operated at appropriate temperatures. Thermal efficiency of reversible hydrogenation based thermal energy storage can reach values up to 65.9% and an overall efficiency of up to 23.1% compared to 25.7% without heat storage. The LOHC dibenzyltoluene and the metal hydride magnesium hydride turn out to be most suitable for this application. (C) 2015 Elsevier Ltd. All rights reserved.
Keywords: Thermal energy storage; LOHC; Metal hydride; Thermodynamics

Water Removal from LOHC Systems - Müller, Karsten; Aslam, Rabya; Fikrt, André; Krieger, Christoph; Arlt, Wolfgang (Hydrogen, 2020)
Liquid organic hydrogen carriers (LOHC) store hydrogen by reversible hydrogenation of a carrier material. Water can enter the system via wet hydrogen coming from electrolysis as well as via moisture on the catalyst. Removing this water is important for reliable operation of the LOHC system. Different approaches for doing this have been evaluated on three stages of the process. Drying of the hydrogen, before entering the LOHC system itself, is preferable. A membrane drying process turns out to be the most efficient way. If the water content in the LOHC system is still so high that liquid–liquid demixing occurs, it is crucial for water removal to enhance the slow settling. Introduction of an appropriate packing can help to separate the two phases as long as the volume flow is not too high. Further drying below the rather low solubility limit is challenging. Introduction of zeolites into the system is a possible option. Water adsorbs on the surface of the zeolite and moisture content is therefore decreased.
CRIS-Team Scopus Importer:2024-12-16
Keywords: dibenzyl toluene; drying; hydrogen storage; LOHC; phase separation; purification